2010
DOI: 10.1192/apt.bp.108.006205
|View full text |Cite
|
Sign up to set email alerts
|

Tattoos: what is their significance?

Abstract: SummaryThe prevalence of tattoos is higher among people with mental disorders and those likely to come in contact with mental health services. The motivations for acquiring a tattoo are varied and tattoos can give clues to the presence of particular psychiatric conditions and to the inner world of patients. Psychiatrists need to be aware of the health and safety issues surrounding the tattooing procedure and be able to give appropriate advice to their patients if they wish to acquire a tattoo. The issue of cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although several studies have indicated a greater prevalence of tattoos among psychiatric samples compared to the general population, the data to support this conclusion are largely drawn from older studies based on comparisons of cross-sectional measures of psychopathology among tattooed individuals in either non-psychiatric settings or psychiatric settings with inadequate controls between samples[ 10 ]. For example, Birmingham et al[ 11 ] reported an association between tattoos and a diagnosis of schizophrenia, but their study was based on a limited sample of male prisoners with visible tattoos.…”
Section: What Do Tattoos Tell Us About Their Wearers?mentioning
confidence: 99%
“…Although several studies have indicated a greater prevalence of tattoos among psychiatric samples compared to the general population, the data to support this conclusion are largely drawn from older studies based on comparisons of cross-sectional measures of psychopathology among tattooed individuals in either non-psychiatric settings or psychiatric settings with inadequate controls between samples[ 10 ]. For example, Birmingham et al[ 11 ] reported an association between tattoos and a diagnosis of schizophrenia, but their study was based on a limited sample of male prisoners with visible tattoos.…”
Section: What Do Tattoos Tell Us About Their Wearers?mentioning
confidence: 99%
“…With respect to tattoos, a higher than average prevalence of skin markings has been found among young adults who use mental health services[26,27]. In an early study of visible tattoos on a psychiatric ward, Birmingham et al[28] reported a 30% rate of schizophrenia.…”
Section: Physical Appearancementioning
confidence: 99%
“…As I (Lane, ) have argued, these strands of research overemphasize the relationship between being modified and deviance, immoral behavior, or mental illness. This scholarship continues despite research showing weak, if not contradictory findings (Iannaccone et al, ; Jennings et al, ; Khosla, Joseph, & Harvey, ).…”
Section: Existing Research On Body Modificationmentioning
confidence: 99%